Geodezija in območja vaških, krajevnih in četrtnih skupnosti - Kos, Jože (Geodetski vestnik, 1997)
During the reform of small local communities in the Municipality of Maribor, it was found that the content of certain surveyors' databases could be enriched. This paper therefore offers some suggestions: for example, concerning the city as a new official territorial unit in Slovenia; the definition of different types of human settlements; and about the building up of a special archive for storing the results of political reforms concerning local communities in Slovenia.
Keywords: geodezija; lokalne skupnosti; mesto; naselje; prostorska struktura; Slovenija